PORTFOLIO OPTIMIZATION WITH EUROPE OPTION USING MATRIX ANALYSIS - Zaidan Pradana, Faisal
In every investment, investors desire the highest possible return and the lowest possible risk. If the investment is in the form of a portfolio consisting of a collection of assets, then the role of matrix analysis is needed to model the problem into a matrix or vector. For risky assets (uncertain yield), it is assumed that the return (log) in a period is normally distributed. The data used to estimate distribution parameters can be in the form of real historical data from an asset or simulation of random number generation from computer programming. The parameters to be estimated, namely the mean and variance, are estimated using the moment and maximum likelihood methods. In this final project, Markowitz optimization is studied which utilizes the concept of matrix analysis to determine the optimal asset allocation. Derivative financial instruments such as European options are added to the portfolio so as to reduce investment risk.